Microbial Outlook for the Bioremediation of Crude Oil Contaminated Environments - Rezende, Rachel Passos; Maciel, Bianca Mendes; Dias, João Carlos Teixeira; Souza, Felipe Oliveira (IntechOpen, 2012)
None